(untitled) (The Research of Medical Science Review, 2025)
BACKGROUND:Temporomandibular joint disorders (TMDs) are a prevalent condition causing pain, functional limitations, and reduced quality of life. Conventional non-surgical treatments offer symptom relief but often fail to address underlying joint degeneration. Platelet-rich plasma (PRP) has emerged as a regenerative therapy with potential benefits over traditional approaches. OBJECTIVE:To compare the clinical efficacy of PRP injections with conventional conservative treatments (NSAIDs and physical therapy) in reducing pain and improving jaw function among patients with TMDs. METHODS:A randomized controlled trial was conducted involving two groups: one receiving intra-articular PRP injections and the other undergoing standard conservative management. Pain was assessed using the Visual Analogue Scale (VAS), and functional outcomes included maximal mouth opening and lateral jaw excursion. Additional outcomes included joint sound reduction, patient satisfaction, and number of PRP injections. Data were analyzed using appropriate statistical tests with significance set at p<0.05. Results:The PRP group showed significantly greater reduction in pain (mean VAS score: 2.3 vs 4.6, p<0.001), increased maximal mouth opening (42.5 mm vs 36.4 mm, p=0.004), and improved lateral excursion (8.5 mm vs 6.2 mm, p=0.012) compared to the conventional therapy group. Patient satisfaction, joint sound reduction, and perceived functional improvement were higher in the PRP group. Most patients (60%) required two PRP injections, while 15% improved after a single dose. CONCLUSION:PRP therapy demonstrated superior outcomes in pain reduction, functional improvement, and patient satisfaction compared to conventional conservative treatments in TMDs. These findings support PRP as a promising alternative for the non-surgical management of TMDs